MODEL REGRESI POISSON UNTUK PENDUGAAN FAKTOR-FAKTOR YANG MEMPENGARUHI COVID-19 DI PULAU SUMATERA - Gusmi Kholijah; Niken Rarasati; Corry Sormin (UNEJ e-Proceeding, 2022)
Covid-19 which has hit various countries in the world has become a scary thing for people to do activities outside the home. So that to carry out community activities, they must follow the rules of the health protocol that have been set, such as wearing masks, washing hands and keeping a distance. Covid-19 cases that occur can be spread through interactions between infected people. The interaction between communities is not only carried out in each region, but can be carried out between provinces within a region. The extent of interaction between people at this time can lead to the easy spread of Covid-19 cases. So that the number of COVID-19 cases can appear in several areas. The existence of a relationship between several predictor variables that affect the response variable in the form of count data can be referred to as Poisson regression. The dominant factors that caused the large number of Covid-19 sufferers on the island of Sumatra were the population, poverty level, income, regional temperature, compliance with wearing masks and compliance with maintaining distance. Keyword: Covid 19, Poisson, Regression